Advanced Computing and Systems for Security Volume 2 - Chaki, Rituparna; Cortesi, Agostino; Saeed, Khalid; Chaki, Nabendu; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book contains the extended version of the works that have been presented and discussed in the Second International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2015) held during May 23-25, 2015 in Kolkata, India. The symposium has been jointly organized by the AGH University of Science & Technology, Cracow, Poland; Ca' Foscari University, Venice, Italy and University of Calcutta, India. The book is divided into volumes and presents dissertation works in the areas of Image Processing, Biometrics-based Authentication, Soft Computing, Data Mining, Next Generation Networking and Network Security, Remote Healthcare, Communications, Embedded Systems, Software Engineering and Service Engineering.
Signal Processing: Chapter 1. Design and Development of Marathi Speech Interface System -- Chapter 2. Fusion-based noisy image segmentation method -- Chapter 3. An Approach for Automatic Indic Script Identification from Handwritten Document Images -- Chapter 4. Writer Verification on Bangla Handwritten Characters -- Chapter 5. Face Recognition in Video using Deformable Parts Model with Scale Invariant Feature Transform (DPSIFT) -- Chapter 6. Registration of Range Images using a novel technique of Centroid Alignment -- Software Engineering: Chapter 7. An investigation into effective test coverage -- Chapter 8. Resource Management in Native Languages using Dynamic Binary Instrumentation (PIN) -- Chapter 9. A Study on Software Risk Management Strategies and Mapping with SDLC -- Chapter 10. A New Service Discovery Approach for Community based Web -- Chapter 11. Data-flow Analysis-based Approach of Database Watermarking -- Networking and Cloud Computing: Chapter 12. A New Framework for Configuration Management and Compliance Checking towards Component Based Software Development -- Chapter 13. CAD Based Analysis of Power Distribution Network for SOC Design -- Algorithms: Chapter 14. A New Hybrid Mutual Exclusion Algorithm in Absence of Majority Consensus -- Chapter 15. A Comprehensive Sudoku Instance Generator -- Chapter 16. Impleme nting Software Transactional Memory using STM Haskell -- Chapter 17. Comparative Analysis of Genetic Algorithm and Classical Algorithms in Fractional Programming -- Chapter 18. An Algorithm to Solve 3D Guard Zone Computation Problem -- Chapter 19. Multi-step ahead Groundwater Level Time Series Forecasting using Gaussian Process Regression and ANFIS -- Chapter 20. Anomaly Detection and Three Anomalous Coins Problem.
Keywords: Computational intelligence; Signal processing; Data protection; Computational Intelligence; Signal, Speech and Image Processing; Data and Information Security